2016
DOI: 10.1186/s13584-016-0112-5
|View full text |Cite
|
Sign up to set email alerts
|

Influenza vaccination motivators among healthcare personnel in a large acute care hospital in Israel

Abstract: BackgroundVaccinating healthcare personnel (HCP) against influenza is important to prevent transmission and morbidity among patients and staff.MethodsWe conducted an online survey assessing knowledge, perceptions and attitudes concerning influenza vaccination among HCP. Multivariate logistic regression was performed to identify independent predictors of vaccination.ResultsThe survey was completed by 468 HCP representing all categories of staff. Doctors believed that vaccination was the best way to prevent infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
1
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 14 publications
3
24
1
5
Order By: Relevance
“…It is found out here that the widespread causes of refusing the influenza vaccine were the “fear of vaccine side effects” and the “vaccine ineffectiveness”. These are similar to the other studies worldwide [18, 25]. An Iranian research in 2016 presented that 19.8% of the respondents were concerned about the influenza vaccine side effects [15].…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…It is found out here that the widespread causes of refusing the influenza vaccine were the “fear of vaccine side effects” and the “vaccine ineffectiveness”. These are similar to the other studies worldwide [18, 25]. An Iranian research in 2016 presented that 19.8% of the respondents were concerned about the influenza vaccine side effects [15].…”
Section: Discussionsupporting
confidence: 87%
“…In the current study, 38.9% of the HCPs believed that “they might get flu after influenza vaccination”. In the literature review, the HCPs’ misconception about getting flu after influenza vaccination was different; from as low as 38.1% to as high as 78% [15, 25-27]. The lower rate of the misperception in the present study indicates their higher awareness.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…In a recent article published in the Israel Journal of Health Policy Research, Nutman and Yoeli reported on an assessment of the knowledge, perceptions and attitudes concerning influenza vaccination among HCP in a large tertiary care academic hospital in Israel [14]. The authors obtained their information by means of an anonymous survey completed by 468 HCP representing all categories of staff.…”
Section: Introductionmentioning
confidence: 99%